[OA177] Contribution of the medical physicist to the italian consensus document on management of patients with cardiac implantable devices (CIED) undergoing radiotherapy and future development from aifm wotking group. (August 2018) - Severgnini, Mara; Menegotti, Loris; Delana, Anna; Malatesta, Tiziana; Quattrocchi, Mariagrazia; Aslian, Hossein; Pietrobon, Francesca; Andreoli, Stefano; Cattani, Federica; kaiser, Stefano Ren; Eugenia, Moretti; Foti, Claudio; et al.
Abstract : Purpose: The management of patients with CIED receiving radiotherapy (RT) is challenging and requires a structured multidisciplinary approach. In order to stratify the risk of patients and approaching RT sessions appropriately, a consensus document from Associazione Italiana Aritmologia e Cardiostimolazione (AIAC), Associazione Italiana Radioterapia Oncologica (AIRO), Associazione Italiana Fisica Medica (AIFM) has been published on the International Journal of Cardiology in 2018. Along this line, the AIFM working group is promoting specific measurements to better investigate the role of RT on CIED. Methods: In Consensus document potential radiation interactions on CIED such as recommendations for the estimation of the dose to the device are described and a multidisciplinary review of in vivo and in vitro data is presented. Further, a multi-center study to evaluate IGRT dose, neutron contamination assessment, and photon out-of-field dose are still being performed. To measure out-of-field dose to CIEDs two phantoms were created and sent to centers working with different treatment planning systems (TPS). Results: Preliminary results show that the use of daily CBCT can add a considerable contribution to CIED dose up to 50 cGy like lung 4D protocol. Neutron contamination of photon and electron beams of energies ranging from 6 to 18 MV measured with REM counters show that neutron production for 10 MV photon beam is not negligible. It confirms that neutron produced by electron beam has to be taken into account for beam energy higher than 15 MeV. Comparisons between calculated and measured out-of-filed dose along with examining the behavior of different dosimeters are being studied. Working group is performing measurement to confirm that, in absence of out-of-field TPS commissioning, in vivo dosimetry is still recommended in the case of short distance CIED-field edge or dose close to 2 Gy. Conclusions: A detailed approach for safe management of RT patients with CIEDs is now available with important implications for clinical practice. Only a multidisciplinary approach between medical physicists, radiation oncologists and electrophysiologists can really reduce the risk of malfunctions in patient with CIED undergoing RT. Results of the AIFM working group try to provide valuable support and further indications in this regard.